2022
DOI: 10.1055/s-0042-1742734
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Venous Thromboembolism Prophylaxis May Not Be Necessary for DIEP Flap Breast Reconstruction: A Tertiary Center's 10-Year Experience

Abstract: Background Based on the 2005 Caprini Risk Assessment Model for venous thromboembolism, the American Society of Plastic Surgeons prevention guidelines would result in prolonged chemoprophylaxis (1 week or more) for the majority of patients undergoing deep inferior epigastric perforator flap breast reconstruction. We aim to assess the necessity of prolonged prophylaxis by describing our institutional experience in thromboembolism prevention and evaluating the incidence of symptomatic VTE in our patient cohort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 36 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Therefore, appropriate perioperative and postoperative coagulopathy prophylaxis is imperative for patients undergoing autologous breast reconstruction. Whereas the American Society of Plastic Surgeons has released guidelines on chemoprophylaxis for the prevention of postoperative venous thromboembolic events, there has been a great deal of research into risk stratifying patients for thromboembolic events and determining optimal prophylactic regimens 25–29 . The Caprini score was created in 1991 and has served as a helpful tool for assessing thromboembolic risk in surgical patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, appropriate perioperative and postoperative coagulopathy prophylaxis is imperative for patients undergoing autologous breast reconstruction. Whereas the American Society of Plastic Surgeons has released guidelines on chemoprophylaxis for the prevention of postoperative venous thromboembolic events, there has been a great deal of research into risk stratifying patients for thromboembolic events and determining optimal prophylactic regimens 25–29 . The Caprini score was created in 1991 and has served as a helpful tool for assessing thromboembolic risk in surgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the American Society of Plastic Surgeons has released guidelines on chemoprophylaxis for the prevention of postoperative venous thromboembolic events, there has been a great deal of research into risk stratifying patients for thromboembolic events and determining optimal prophylactic regimens. [25][26][27][28][29] The Caprini score was created in 1991 and has served as a helpful tool for assessing thromboembolic risk in surgical patients. It has since been validated across many surgical subspecialties, including plastic and reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines by the ACCP state that for patients at high risk for VTE following hip and knee replacement, prophylaxis should be extended by an additional three weeks. [28][29][30] Furthermore, a review by Huo and Muntz found that the risk of VTE extends past high-risk patients' hospitalizations; extended VTE prophylaxis between 28 and 45 days aids in reducing the risk of late VTE events. 31 Surgeon preferences for anticoagulation of choice, ranging from subcutaneous heparin, enoxaparin, to other agents, varied widely.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, VTE rates did not significantly differ between guideline-consistent and nonconsistent chemoprophylaxis. 17 Conversely, Modarressi et al found in a similar study that over 90 PODs, four patients (2.1%) had pulmonary embolism, and two patients (1%) developed deep venous thrombosis, yielding an overall VTE incidence of 3.1%. Interestingly, most patients (92.2%) had high-risk Caprini scores (>5), and all VTE cases were within this group.…”
Section: Discharge Protocols/erasmentioning
confidence: 93%
“…ASPS recommends VTE prophylaxis for Caprini scores above 3, with prolonged prophylaxis (4 weeks) for scores exceeding 7. 17 Given this recommendation, it would be expected that most, if not all, ASPS surgeons would use the Caprini score to determine VTE prophylaxis for their patients. However, surprising findings indicate a majority of surgeons discontinue prophylaxis upon the patient's discharge from the hospital.…”
Section: Discharge Protocols/erasmentioning
confidence: 99%